PENGARUH AUDIT OPERASIONAL DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN - Novaya Eky Aidha Pravitasari; Nur Diana; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
The purpose of this study is to provide empirical evidence about the effect of operational audit and internal control on employee performance. This study uses primary data by distributing questionnaires. The population used is workers who have positions such as the operational section, the finance section and the business resources section at PT. Sinar Waringin Adikarya or SWA Builders Surabaya. The sampling technique used purposive sampling method with respondent criteria determined by the correlational model. Hypothesis testing in this study used the simultaneous test (F test), the coefficient of determination (R^2), and the partial test (t-test). From the results of this study, it is interpreted that the operational audit and internal control variables simultaneously affect employee performance. In partial testing the operational audit does not have a positive effect, while control has a positive effect on employee performance. Keywords: Operational Audit, Internal Control and Employee Performance.